2021
DOI: 10.31729/jnma.6132
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety among Nursing Students towards Clinical Placement during COVID-19 in a Tertiary Hospital of Nepal: A Descriptive Cross-sectional Study

Abstract: Introduction: The world is facing the pandemic of COVID-19 caused by the corona virus since December 2019 and has caused millions of death throughout the world. Exposure of nursing students in clinical placement during pandemic is fearful and stressful with high risk of infection which can cause anxiety and different levels of psychological crisis to individuals. The main objective of the study is to find out the prevalence of anxiety among nursing students during clinical placement in the pandemic of COVID-19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Table 1 shows the overall characteristics of the 41 included studies ( Elhadi et al, 2020 ; Jindal et al, 2020 ; Liu et al, 2020 ; Medeiros et al, 2020 ; Muhammad Alfareed Zafar et al, 2020 ; Nadeem et al, 2020 ; Nakhostin-Ansari et al, 2020 ; Nihmath Nisha et al, 2020 ; Sartorao Filho Carlos et al, 2020 ; Sun et al, 2020 ; Adhikari et al, 2021 ; Banstola et al, 2021 ; Basheti et al, 2021 ; Bilgi et al, 2021 ; Gao et al, 2021 ; Guo et al, 2021 ; Gupta et al, 2021 ; Halperin et al, 2021 ; Kalkan Uğurlu et al, 2021 ; Kaplan Serin and Doğan, 2021 ; Keskin, 2021 ; Kuman Tunçel et al, 2021 ; Li et al, 2021 ; Mekhemar et al, 2021 ; Meng et al, 2021 ; Nishimura et al, 2021 ; Patelarou et al, 2021 ; Pavan et al, 2021 ; Pelaccia et al, 2021 ; Perissotto et al, 2021 ; Saeed and Javed, 2021 ; Safa et al, 2021 ; Song et al, 2021 ; Xiao et al, 2021 ; Xie et al, 2021 ; Yadav et al, 2021 ; Yang et al, 2021 ; Yin et al, 2021 ; Zhang et al, 2021a ; Zheng et al, 2021 ; Zhu et al, 2021 ). On the whole, 40 cross-sectional studies and 1 longitudinal study were included in our study.…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 shows the overall characteristics of the 41 included studies ( Elhadi et al, 2020 ; Jindal et al, 2020 ; Liu et al, 2020 ; Medeiros et al, 2020 ; Muhammad Alfareed Zafar et al, 2020 ; Nadeem et al, 2020 ; Nakhostin-Ansari et al, 2020 ; Nihmath Nisha et al, 2020 ; Sartorao Filho Carlos et al, 2020 ; Sun et al, 2020 ; Adhikari et al, 2021 ; Banstola et al, 2021 ; Basheti et al, 2021 ; Bilgi et al, 2021 ; Gao et al, 2021 ; Guo et al, 2021 ; Gupta et al, 2021 ; Halperin et al, 2021 ; Kalkan Uğurlu et al, 2021 ; Kaplan Serin and Doğan, 2021 ; Keskin, 2021 ; Kuman Tunçel et al, 2021 ; Li et al, 2021 ; Mekhemar et al, 2021 ; Meng et al, 2021 ; Nishimura et al, 2021 ; Patelarou et al, 2021 ; Pavan et al, 2021 ; Pelaccia et al, 2021 ; Perissotto et al, 2021 ; Saeed and Javed, 2021 ; Safa et al, 2021 ; Song et al, 2021 ; Xiao et al, 2021 ; Xie et al, 2021 ; Yadav et al, 2021 ; Yang et al, 2021 ; Yin et al, 2021 ; Zhang et al, 2021a ; Zheng et al, 2021 ; Zhu et al, 2021 ). On the whole, 40 cross-sectional studies and 1 longitudinal study were included in our study.…”
Section: Resultsmentioning
confidence: 99%
“…The intervention had positive results, and effective alternatives to conventional psychotherapy included behavioral therapy and online mindfulness programs ( Liang et al, 2021 ; Simonsson et al, 2021 ). Some studies have suggested that positive approach coping strategies for COVID-19 are better than negative avoidance coping strategies in improving stress and anxiety ( Banstola et al, 2021 ; Chan et al, 2022 ). A review of the literature identified 18 articles related to COVID-19, anxiety, stress, and the effects of different interventions (all studies are summarized in Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Lovecraft wrote: “The oldest and strongest emotion of mankind is fear, and the oldest and strongest kind of fear is fear of the unknown” ( Joshi and Schultz, 2001 ; p. 255). Therefore, among the 18 included studies, five were of the opinion that we should actively face COVID-19 and that increasing its understanding through various means would help reduce students’ stress and anxiety ( Banstola et al, 2021 ; Kheirallah et al, 2021 ; Simegn et al, 2021 ; Yildirim et al, 2021 ; Chan et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations